2016
DOI: 10.1038/srep21299
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of germinated wheat grains using terahertz image and chemometrics

Abstract: In this paper, we propose a feasible tool that uses a terahertz (THz) imaging system for identifying wheat grains at different stages of germination. The THz spectra of the main changed components of wheat grains, maltose and starch, which were obtained by THz time spectroscopy, were distinctly different. Used for original data compression and feature extraction, principal component analysis (PCA) revealed the changes that occurred in the inner chemical structure during germination. Two thresholds, one indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…The fusion process is shown in Figure 2 . The feature information of the sample was obtained, and then the support vector machine [ 36 , 37 ] using the radial basis kernel function was used to train the feature information. Then the corresponding sub-classifiers, RBF-SVM (absorption coefficient) and RBF-SVM (refractive index), were constructed.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The fusion process is shown in Figure 2 . The feature information of the sample was obtained, and then the support vector machine [ 36 , 37 ] using the radial basis kernel function was used to train the feature information. Then the corresponding sub-classifiers, RBF-SVM (absorption coefficient) and RBF-SVM (refractive index), were constructed.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In the past decade, new emerging approach of THz spectroscopy – THz time-domain spectroscopy (TDS) in combination with chemometrics techniques in particular 6 – showed a significant breakthrough in application for food quality inspection 12 . A number of studies has recently reported promising results that are addressed to the discrimination of transgenic crops 13,14 , early wheat grains germination detection 15 , the determination of tea types with the protected geographical indications 16 , as well as the discrimination between edible oils and used frying oils 17 . Recently, Yin et al .…”
Section: Introductionmentioning
confidence: 99%
“…Diferent types of thermal building insulation materials are analyzed [90]. (ii) TPI and THz-TDS are used to identify wheat grains at diferent stages of germination [91]. Speciically, the inner chemical structure during germination can be revealed from the THz spectra.…”
Section: Other Applicationsmentioning
confidence: 99%